Structural study of a series of synthetic goethites obtained in aqueous solutions containing cadmium(II) ions - Sileo, E. E.; Solis, P. S.; Paiva-Santos, C. O. (J C P D S-int Centre Diffraction Data, 2003)
The capacity of goethite for Cd-II substitution has been explored in a series of synthetic samples prepared from Fe-III and Cd-II nitrate solutions aged 21 days in alkaline media. The total metal content ([ Fe] + [ Cd]) was 0.071 M in all preparations. The samples have been characterized by chemical and X-ray diffraction analysis; the morphology of the solids is described. The cell parameters for all samples were obtained by the Rietveld fits to the X-ray diffraction data. Refined structures show that for samples prepared at the final molar ratio mu(Cd)less than or equal to5.50 (expressed as mu(Cd) = 100X[Cd]/[Cd] + [Fe]), a (Cd, Fe)-goethite is the only crystalline product. In these samples, the unit cell parameters increased as a function of Cd concentration, indicating Cd incorporation in the structural frame. At the preparative ratio, mu(Cd)=7.03, the incorporation of Cd in the goethite structure is drastically reduced and a probable Cd-substituted hematite is formed together with the Fe,Cd-goethite. (C) 2003 International Centre for Diffraction Data.
Keywords: X-ray powder diffraction; Rietveld analysis; substituted goethite; cadmium; substituted hematite